2013
DOI: 10.5586/asbp.2013.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of medicinal plant Schisandra chinensis using a potential DNA barcode ITS2

Abstract: IntroductionSchisandra chinensis (Turcz.) Baill. grows mainly in the northeast China and its mature fruits are famous traditional Chinese medicine recorded in "Chinese Pharmacopoeia". As a traditional medicinal herb, S. chinensis has been used as an astringent curing dry cough, asthma, night sweats, nocturnal seminal emissions and chronic diarrhea [1,2]. Modern medical research had proved that S. chinensis contains multiple active components used to protect liver [3][4][5], prevent senility [6][7][8][9], restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In respect to the authentication of medicinal plants, there were 24 Chinese medicinal plants of Schisandraceae, nine species of Schisandra , three of Kadsura , and 12 of Illicium successfully discriminated via one or more diagnostic methods by single locus or multi-locus combinations in this study ( S9 Table ). Taking important medicinal plants for example, for Schisandra chinensis , the ITS region that could provide more diagnostic characters for this species than other regions was more suitable for its authentication ( S5 – S8 Tables), which has also been supported by the study of Li et al [ 55 ]. For Illicium verum , ITS and matK were more suitable for its authentication, and they could easily distinguish this species from others using the diagnostic characters through visual examination of the alignments ( S5 – S8 Tables).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In respect to the authentication of medicinal plants, there were 24 Chinese medicinal plants of Schisandraceae, nine species of Schisandra , three of Kadsura , and 12 of Illicium successfully discriminated via one or more diagnostic methods by single locus or multi-locus combinations in this study ( S9 Table ). Taking important medicinal plants for example, for Schisandra chinensis , the ITS region that could provide more diagnostic characters for this species than other regions was more suitable for its authentication ( S5 – S8 Tables), which has also been supported by the study of Li et al [ 55 ]. For Illicium verum , ITS and matK were more suitable for its authentication, and they could easily distinguish this species from others using the diagnostic characters through visual examination of the alignments ( S5 – S8 Tables).…”
Section: Discussionmentioning
confidence: 56%
“…The ITS region has been treated as one of the most appropriate DNA barcodes because of its higher variability, which might enhance identification rates even in closely related species [ 12 , 13 ]. Previous studies have suggested that ITS/ITS2 is able to discriminate several Schisandra species [ 55 , 56 ]. In addition, trnH-psbA has been suggested as a promising locus in many studies [ 14 , 95 98 ], including some on medicinal plants [ 99 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest advancement in the DNA sequencing technology and bioinformatics tools for DNA sequence data analysis lead to the development of DNA barcoding techniques (Hebert et al, 2003, Hebert et al, 2004, Hebert and Gregory, 2005, Hebert and Barrett, 2005, Ali et al, 2014) which have revolutionaries the method of the plant taxonomic identification (Poczai and Hyvönen, 2010) using DNA barcoding method especially based on DNA barcode sequence such as nrDNA ITS1, nrDNA ITS2 (Chen et al, 2010, Yao et al, 2010), rbcL, matK, ycf5, rpoC1, psbA-trnH, rps16, trnL-F and ndhF ( Ali et al, 2014). DNA barcoding have successfully employed in authentication of Crocus sativus (Jiang et al, 2014), Schisandra chinensis (Li et al, 2013), Astragalus (Gao et al, 2009). The Next Generation Sequencing (NGS) is comparatively new, and have been demonstrated in the authentication of Costus pictus (Annadurai et al, 2012), Aconitum (Yun et al, 2015), Dendrobium officinale (Guo et al, 2013), Huperzia serrata and Phlegmariurus carinatus (Luo et al, 2010), Valeriana officinalis (Pyle et al, 2012), Hippophae rhamnoides (Ghangal et al, 2013), Ocimum sanctum (Rastogi et al, 2015), Beta vulgaris (Dohm et al, 2014), Panax ginseng (Jayakodi et al, 2014), Elaeis guineensis (Singh et al, 2013), Curcuma longa (Annadurai et al, 2013), Catharanthus roseus (Van Moerkercke et al, 2013), Withania somnifera (Gupta et al, 2013), Azadirachta indica (Krishnan et al, 2012), Cannabis sativa (van Bakel et al, 2011) and Populus trichocarpa (Tuskan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…There are currently about 80 species of Schisandraceae, including 34 medicinal plants [ 20 , 21 ]. The commonly used agents in Schisandraceae are found in S. chinensis and S. sphenanthera , and many methods can be used for identification, like chemistry and molecular pharmacy [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%